A new model measuring bacterial phagocytosis and phagolysosomal oxidation in humans using the intradermal injection of methylene blue-labeled Escherichia coli - Collins, George B.; de Souza Carvalho, Jhonatan [UNESP]; Jayasinghe, Sandali C.; Gumuliauskaite, Urte; Lowe, David M.; Thomas, David C.; Årstad, Erik; De Maeyer, Roel P H; Gilroy, Derek W. (Oxford University Press (OUP), 2025)
Phagocytosis is an important leukocyte function; however, using existing models it cannot be measured in human tissues in vivo. To address this, we characterized a new phagocytosis model using intradermal methylene blue-labeled Escherichia coli injection (MBEC). Methylene blue (MB) is a licensed human medicine and bacterial stain potentially useful for labeling E. coli that is safe for human injection. Ex vivo coculture of leukocytes with MBEC caused MB to transfer into neutrophils and macrophages by phagocytosis. During this, a red shift in MB fluorescence was shown to be caused by phagolysosomal oxidation. Hence, MBEC coculture could be used to measure phagocytosis and phagolysosomal oxidation in humans, ex vivo. In healthy volunteers, inflammatory exudate sampling using suction blisters 2 to 24 h after intradermal MBEC injection showed that tissue-acquired neutrophils and monocytes contained more MB than their circulating counterparts, whereas blood and inflamed tissue T, B, and natural killer cells were MBlo. This was validated with spectral flow cytometry by visualizing the MB emission spectrum in tissue-acquired neutrophils. Neutrophil MB emission spectra demonstrated more red shift at 24 h compared with earlier time points, in keeping with progressive phagolysosomal MB oxidation in neutrophils over time in vivo. This new MBEC model can therefore measure bacterial phagocytosis and phagolysosomal oxidation in human skin, in vivo. This has a number of important research applications, e.g. in studying human phagocyte biology, testing novel antimicrobials, and understanding why certain groups such as males, the elderly or those with diabetes, recent surgery, or malnutrition are at increased risk of bacterial infection.
Keywords: human challenge models; infection; neutrophils; phagocytosis; phagolysosomal oxidation